Effect of Interaction between 17β-Estradiol, 2-Methoxyestradiol and 16α-Hydroxyestrone with Chromium (VI) on Ovary Cancer Line SKOV-3: Preliminary Study - Ewa Sawicka; Jolanta Saczko; Joanna Roik; Julita Kulbacka; Agnieszka Piwowar (Molecules, 2020)
Ovarian cancer is the leading cause of death from gynecologic malignancies. Some estrogens, as well as xenoestrogens, such as chromium (VI) (Cr(VI)), are indicated as important pathogenic agents. The objective of this study was to evaluate the role of estradiol and some its metabolites upon exposure to the metalloestrogen Cr(VI) in an in vitro model. The changes in cell viability of malignant ovarian cancer cells (SKOV-3 resistant to cisplatin) exposed to 17β-estradiol (E2) and its two metabolites, 2-methoxyestradiol (2-MeOE2) and 16α-hydroxyestrone (16α-OHE1), upon exposure to potassium chromate (VI) and its interactions were examined. The single and mixed models of action, during short and long times of incubation with estrogens, were applied. The different effects (synergism and antagonism) of estrogens on cell viability in the presence of Cr(VI) was observed. E2 and 16α-OHE1 caused a synergistic effect after exposure to Cr(VI). 2-MeOE2 showed an antagonistic effect on Cr(VI). The examined estrogens could be ranked according to the most protective effect or least toxicity in the order: 2-MeOE2 > E2 > 16α-OHE1. Early pre-incubation (24 h or 7 days) of cells with estrogens caused mostly an antagonistic effect—protective against the toxic action of Cr(VI). The beneficial action of estrogens on the toxic effect of Cr(VI), in the context of the risk of ovarian cancer, seems to be important and further studies are needed.